2014
DOI: 10.1161/jaha.114.001053
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Care Transition Measure in TRACE‐CORE: Do We Need a Better Measure?

Abstract: BackgroundThe quality of transitional care is associated with important health outcomes such as rehospitalization and costs. The widely used Care Transitions Measure (CTM‐15) was developed with a classic test theory approach; its short version (CTM‐3) was included in the CAHPS Hospital Survey. We conducted a psychometric evaluation of both measures and explored whether item response theory (IRT) could produce a more precise measure.Methods and ResultsAs part of the Transitions, Risks, and Actions in Coronary E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 33 publications
4
25
2
6
Order By: Relevance
“…By 8 weeks, when we conducted the present survey, some patients probably avoided visits to the emergency department or re‐hospitalizations by receiving support from outpatient services. A previous study showed that other assessment tools, aside from the J‐CTM‐15, are therefore more suitable to assess the necessity of visits to the emergency department …”
Section: Discussionmentioning
confidence: 99%
“…By 8 weeks, when we conducted the present survey, some patients probably avoided visits to the emergency department or re‐hospitalizations by receiving support from outpatient services. A previous study showed that other assessment tools, aside from the J‐CTM‐15, are therefore more suitable to assess the necessity of visits to the emergency department …”
Section: Discussionmentioning
confidence: 99%
“…Al usar la herramienta CTM-3 existe una tendencia entre los encuestados a contestar de forma afirmativa a las preguntas, es decir, a no entrar en conflicto con el encuestador, y afirmar que todo el proceso ha sido satisfactorio (10). Esta deficiencia en la encuesta CTM-3 original se relaciona con la presencia de cinco posibles respuestas muy parecidas entre sí, por lo que el encuestado encontraba dificultades para responder.…”
Section: Discussionunclassified
“…Esta deficiencia en la encuesta CTM-3 original se relaciona con la presencia de cinco posibles respuestas muy parecidas entre sí, por lo que el encuestado encontraba dificultades para responder. En la encuesta CTM-3-modificada se redujo el número de opciones de respuesta, con lo que es presumible que el sesgo de aquiescencia se haya reducido (10,12). En relación con los resultados obtenidos, cabe destacar que la satisfacción con la continuidad de cuidados se relacionó de forma positiva con el tiempo de estancia hospitalaria, resultado que corrobora el obtenido en investigaciones similares (5, 6).…”
Section: Discussionunclassified
See 2 more Smart Citations